Simulation‐based education: understanding the socio‐cultural complexity of a surgical training 'boot camp'. Issue 8 (August 2016) - Cleland, Jennifer; Walker, Kenneth G; Gale, Michael; Nicol, Laura G
Abstract : Objective: The focus of simulation‐based education (SBE) research has been limited to outcome and effectiveness studies. The effect of social and cultural influences on SBE is unclear and empirical work is lacking. Our objective in this study was to explore and understand the complexity of context and social factors at a surgical boot camp (BC). Methods: A rapid ethnographic study, employing the theoretical lenses of complexity and activity theory and Bourdieu's concept of 'capital', to better understand the socio‐cultural influences acting upon, and during, two surgical BCs, and their implications for SBE. Over two 4‐day BCs held in Scotland, UK, an observer and two preceptors conducted 81 hours of observations, 14 field interviews and 11 formal interviews with faculty members ( n  =   10, including the lead faculty member, session leaders and junior faculty members) and participants ( n  =   19 core surgical trainees and early‐stage residents). Results: Data collection and inductive analysis for emergent themes proceeded iteratively. This paper focuses on three analytical themes. First, the complexity of the surgical training system and wider health care education context, and how this influenced the development of the BC. Second, participants' views of the BC as a vehicle not just for learning skills but for gaining 'insider information' on how best to progress in surgical training. Finally, the explicit aim of faculty members to use the Scottish Surgical Bootcamp to welcome trainees and residents into the world of surgery, and how this occurred. Conclusions: To the best of our knowledge, this is the first empirical study of a surgical BC that takes a socio‐cultural approach to exploring and understanding context, complexities, uncertainties and learning associated with one example of SBE. Our findings suggest that a BC is as much about social and cultural processes as it is about individual, cognitive and acquisitive learning. Acknowledging this explicitly will help those planning similar enterprises and open up a new perspective on SBE research. Abstract : Discuss ideas arising from the article atwww.mededuc.com discuss.